Ethnic disparity in mental health legislation at the point of inpatient entry: pilot review in detained adolescents with developmental disorders. Issue 3 (4th August 2021) - Morris, Deborah J.; Webb, Elanor Lucy; Foster-Davies, Lowri; Wallang, Paul M.; Gibbs, David; McAllister, Peter D.; Shaddel, Farshad
Abstract : Purpose: Ethical concerns about the use of the Mental Health Act (MHA) have led to calls for developmental disorders to be removed from the list of mental disorders for which individuals can be detained. In parallel, there are long-standing concerns of ethnic disparity in the application of the MHA. Nonetheless, the impact of the intersections of developmental disorder diagnosis, adolescence and ethnicity on the application of the MHA is unknown. This study aims to explore ethnic differences in MHA sections and the factors accounting for this, in an adolescent inpatient developmental disorder service. Design/methodology/approach: File reviews were conducted to explore differences in MHA status, as well as demographic, clinical and risk factors that may account for this, between 39 white British and ethnic minority adolescents detained to a specialist inpatient developmental disorder service. Findings: Consistent with adult literature, adolescents of an ethnic minority were overrepresented in the sample and were significantly more likely to be detained on Part III or "forensic" sections of the MHA than White British counterparts, with five times greater risk. Analyses revealed no significant differences between ethnic minority and white British participants on demographic variables, clinical needs, risk behaviours, risk measures nor application of restrictive practices and safeguarding procedures. Practical implications: National audits exploring patterns of detention under the MHA across adolescent developmental disorder populations need to include analysis of intersections to ensure that the MHA is used as a means of last resort and in an equitable manner. Originality/value: To the best of the authors' knowledge, this paper is the first comprehensive exploration of the impact of ethnicity on detention patterns in ethnic minority and White British populations.